2012
DOI: 10.4236/msa.2012.39093
|View full text |Cite
|
Sign up to set email alerts
|

Ion and Gas Nitriding Applied to Steel Tool for Hot Work X38CrMoV5 Nitriding Type: Impact on the Wear Resistance

Abstract: The present work is to characterize both processes of thermochemical treatments: plasma nitriding and gas. The tests were carried out in collaboration with the Franco-Tunisian heat treatment (F3T) applied to a widely used steel in industrial production as a tool for hot work on X38CrMoV5 (AISI H13). The material underwent a first cycle of hardening heat treatment at 1030℃ followed by two successive incomes at 550℃ and 590℃. After nitriding (ion and gas), the quantification of wear was performed in the laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As the temperature increases, the saturation with carbon increases and with nitrogen decreases. At the specified temperature, the surface layer contains ~ 1.0 % C and 0.5 % N [25]. Despite the lower process temperature compared to carburizing, the saturation rate remains almost the same -0.15 mm/h.…”
Section: Statement Of the Goal And Objectives Of The Studymentioning
confidence: 99%
“…As the temperature increases, the saturation with carbon increases and with nitrogen decreases. At the specified temperature, the surface layer contains ~ 1.0 % C and 0.5 % N [25]. Despite the lower process temperature compared to carburizing, the saturation rate remains almost the same -0.15 mm/h.…”
Section: Statement Of the Goal And Objectives Of The Studymentioning
confidence: 99%
“…The optimum result is obtained at the temperature of 800 0 C in 5 hours [8][9]. Ben Slima [10] showed that stiffening before ion and gas nitriding to the tool steel material improve the depth of white layers. Multistage nitridation at 550 0 C and 530 0 C on the H13 steel make the white layer appear in the surface of the material at 5 micron caused by the highest nitrogen concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The high hardness of the SP-N-SP process occurs because nitrogen diffuses into the material based on an interstitial basis, and reacts to form compounds with nitride former elements that are dispersed evenly as nitride (Slima, 2012). Because the process were diffusion process, the hardness value will decrease as the distance from the surface increases.…”
mentioning
confidence: 99%